Efek Perubahan Nilai SWR Pada Siaran Televisi Mobil - roni kartika pramuyanti (Retii, 2021)
There is some signal which is take effect to the antena among others SWR the Standing Wave Ratio which is a comparison or ratio of the existing resistance in a circuit, which is a comparison between the external resistance and the internal resistance. Calculation or the magnitude of this comparison or ratio will have an effect on the existing circuit.The magnitude of the SWR value has been classified in the name of ideal, less ideal or not ideal. The influence of the SWR value that has been summarized in a classification will certainly have a felt effect for the user of the tool or instrument that has the SWR value. With the classification that has been summarized previously coupled with existing calculations, the influence of the magnitude of the SWR value will be explained.Before getting a bad influence or effect from the SWR value, the user will be able to anticipate or prevent the bad thing from happening. In addition, there is a possibility that users can also eliminate or minimize the occurrence of such disturbances or unfavorable influences. By knowing all the disturbances, the user will be able to prevent it so that everything that happens is as expected. From what has happened, the data will conclude about the effect of the SWR value on car television broadcasts which are directly related to the antenna. Keywords: SWR, Standing Wave Ratio, Ideal, Classification, Car Television